Extracellular vesicles containing oncogenic mutant β-catenin activate Wnt signalling pathway in the recipient cells. Issue 1 (1st December 2019) - Kalra, Hina; Gangoda, Lahiru; Fonseka, Pamali; Chitti, Sai V.; Liem, Michael; Keerthikumar, Shivakumar; Samuel, Monisha; Boukouris, Stephanie; Al Saffar, Haidar; Collins, Christine; Adda, Christopher G.; Ang, Ching-Seng; et al.
ABSTRACT: Mutations in β-catenin, especially at the residues critical for its degradation, render it constitutively active. Here, we show that mutant β-catenin can be transported via extracellular vesicles (EVs) and activate Wnt signalling pathway in the recipient cells. An integrative proteogenomic analysis identified the presence of mutated β-catenin in EVs secreted by colorectal cancer (CRC) cells. Follow-up experiments established that EVs released from LIM1215 CRC cells stimulated Wnt signalling pathway in the recipient cells with wild-type β-catenin. SILAC-based quantitative proteomics analysis confirmed the transfer of mutant β-catenin to the nucleus of the recipient cells. In vivo tracking of DiR-labelled EVs in mouse implanted with RKO CRC cells revealed its bio-distribution, confirmed the activation of Wnt signalling pathway in tumour cells and increased the tumour burden. Overall, for the first time, this study reveals that EVs can transfer mutant β-catenin to the recipient cells and promote cancer progression.